Overview of risks associated with heavy rainfall in Niterói - RJ (International Seven Journal of Multidisciplinary, 2024)
Natural disasters are surprising events that cause immeasurable losses, and it is a topic that has been discussed worldwide. Intense and/or prolonged precipitation can cause disasters, catastrophes of gigantic proportions. In Brazil, the Southeast, South and Northeast regions suffer from this problem more recurrently. Inserted in this context, Niterói, one of the most important cities in the State of Rio de Janeiro, presents, especially in the summer months, disasters associated with intense and/or prolonged rains, such as flooding, flash floods and mass movements. This work presents an overview of these disasters and their evolution in recent years, with the purpose of contributing to a better understanding of the risks associated with these disasters and the impacts on the urban site of the Municipality of Niterói. From the panorama presented, it can be seen that the city remains vulnerable to the event of intense rain, since the associated disasters occur frequently in the same affected locations, which points to a possible lack of risk mitigation in most places that present this recurrent behavior.